Multiprotocol Label Switching in Vehicular Ad hoc Network for QoS - Qureshi, Kashif Naseer (Information Management and Business Review, 2014)
Vehicular Ad hoc Networks (VANET) provides a wireless communication between vehicles. VANET applications play a significant role in the transportation sector such as vehicle safety, environmental efficiency, traffic control etc. Vehicular Ad hoc network is a subclass of Mobile Ad hoc networks. One of the main concerns in transportation is quality of service (QoS). In VANET, various solutions proposed for quality of services and these solutions applied on layer 2 and layer 3. In this paper, we proposed a Multiprotocol Label Switching. MPLS is an efficient and effective technique that forwards the packets across the network by using the contents of the labels attached to the IP packets. MPLS is known to be a layer 2.5 technology because it supports both data link layer or layer-2 and layer-3. The use of MPLS as backbone networks has increased over the past few years as compared to traditional IP networks, which were based on Iayer-2 technologies. MPLS is a forwarding method used for backbone network. In this paper, we improve quality of service in term of delay, packet loss and throughput in highway areas.